National surveillance programme on susceptibility patterns of respiratory pathogens in South Africa: moxifloxacin compared with eight other antimicrobial agents. Issue 5 (1st May 2003) - Liebowitz, L D; Slabbert, M; Huisamen, A
Abstract : Aims: The susceptibility patterns of Streptococcus pneumoniae, Haemophilus influenzae, Moraxella catarrhalis, Klebsiella pneumoniae, and Streptococcus pyogenes isolated from specimens submitted to 12 private laboratories in South Africa were determined. Methods: Minimum inhibitory concentration (MIC) determinations were performed on the isolates in the microbiology laboratory at Tygerberg Hospital according to the recommendations of the National Committee for Clinical Laboratory Standards (NCCLS). Results: According to the NCCLS breakpoints, 24% of 729 S pneumoniae isolates were sensitive, 30% intermediate, and 46% resistant to penicillin. Rates of macrolide resistance were high, with 61% of the pneumococci being resistant to clarithromycin and azithromycin. Co-trimoxazole resistance was also high, with 28% of pneumococcal strains being sensitive, 21% intermediate, and 51% resistant. β Lactamase was produced by 7% of 736 H influenzae isolates and 91% of 256 M catarrhalis isolates. The quinolones, moxifloxacin and levofloxacin, were universally active against all isolates tested, which included S pneumoniae, H influenzae, M catarrhalis, K pneumoniae, and S pyogenes . Conclusions: Haemophilus influenzae and S pneumoniae were the most commonly isolated organisms. Resistance to penicillin was one of the highest reported in the world (76%) in S pneumoniae, as was macrolide resistance in pneumonocci, although surprisingly, only 14% of S pyogenes were resistant. The quinolones, moxifloxacin and levofloxacin, were active against all organisms tested, including the penicillin and macrolide resistant strains and moxifloxacin was more active than levofloxacin against pneumococci.